Spectrophotometric Studies on Removal of Brilliant Cresyl Blue From Aqueous Solution by Using Lead Sulphide - Srinivas, Ch.; Nagamani, Ch.; Gangadhar, M.; Raja Sekhar, M. (Asian Journal of Chemistry, 2010)
The present research work deals with the bleaching of brilliant cresyl blue (BCB) dye has been carried out in presence of semiconductor, lead sulphide. The source used for energy is visible light. Various parameters like dosage of lead sulphide, pH, concentration of brilliant cresyl blue dye are studied. Experiments are carried out to remove the brilliant cresyl blue dye stuff by using lead sulphide. It is observed that the dye concentration increases with the decrease in bleaching rate. For an amount of 0.10 g and at a pH value of 8 of PbS the bleaching rate is maximum and found to be decreasing with increasing pH and amount of PbS. The maximum bleaching rate is observed at the optimum time at 75 min. Brilliant cresyl blue dye was removed up to 79.3 % by using semiconductor, lead sulphide.